If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 8)(x + -8) = 0 Reorder the terms: (8 + 2x)(x + -8) = 0 Reorder the terms: (8 + 2x)(-8 + x) = 0 Multiply (8 + 2x) * (-8 + x) (8(-8 + x) + 2x * (-8 + x)) = 0 ((-8 * 8 + x * 8) + 2x * (-8 + x)) = 0 ((-64 + 8x) + 2x * (-8 + x)) = 0 (-64 + 8x + (-8 * 2x + x * 2x)) = 0 (-64 + 8x + (-16x + 2x2)) = 0 Combine like terms: 8x + -16x = -8x (-64 + -8x + 2x2) = 0 Solving -64 + -8x + 2x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(-32 + -4x + x2) = 0 Factor a trinomial. 2((-4 + -1x)(8 + -1x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4Subproblem 2
Set the factor '(8 + -1x)' equal to zero and attempt to solve: Simplifying 8 + -1x = 0 Solving 8 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1x = 0 + -8 -1x = 0 + -8 Combine like terms: 0 + -8 = -8 -1x = -8 Divide each side by '-1'. x = 8 Simplifying x = 8Solution
x = {-4, 8}
| 8+6=x-14 | | -32-41= | | (7x+7)(x-3)=0 | | -18=10z-10/5 | | 3y+2-y=29-y+9 | | 13=-16-x/4 | | -3/5=x-2/7 | | 6-8=x+14 | | 8.3=logI | | 6n+26-4n=54 | | 6x-72=11x | | 15=34-3x | | -7x^2-6=-5x | | 8(2x^2-3x+18)=135 | | -7w-3-4+2w= | | -7x^2-6=5x | | -x^3-7x^2-8x=0 | | 19(6c-1)-16=112c+19 | | 15+0.20m=25+0.10m | | -8+7(0)=-8 | | 5z-8-6z-9= | | (6x^-2)/(3x^2)= | | 2g-12=g+2 | | Y=-(7)+5 | | .66d=5 | | 15m+0.20=25m+0.10 | | -7+7(-3)=-8 | | 5(x+3)=5x-1+16 | | -6+7(-2)=-8 | | -4n-8=-4(n+2) | | V=1/3*3.14*16*11 | | 18÷9/16 |